Inquietudine spettrale Gli uccelli nella concezione poetica di Jacob Grimm - Caprili, Gian Luca (Biblioteca di Studi di Filologia Moderna, 2018)
Inquietudine spettrale. Gli uccelli nella concezione poetica di Jacob Grimm covers a peculiar aspect of Jacob Grimm's poetry: in the framework of a nature pervaded with spirituality, whose hard-to-reach secrets inspire fascination, birds, as inhabitants of the air, are perceived as ghostly creatures, capable of infusing the observer with a sense of restlessness. The individual references to the theme found in essays, letters and works all confirm a strong interest in these animals, and constitute analysis material in the context of Grimm's vast production. Particular recognition is given to the famous collection entitled Kinder- und Hausmärchen (in its first and mostly unknown version), the capital book of the Romantic current in Germany, where the liminal role of birds can be attributed to archaic myths and popular beliefs.